HUBUNGAN TINGKAT KECEMASAN DENGAN HASIL BELAJAR SISWA PADA UJI KOMPETENSI KEAHLIAN - Dwi, Meilinda (STIKES Widyagama Husada, 2025)
In class 12 during the Vocational High School (SMK) period, this is the part that makes students feel very worried. Because there is a test to see how learning achievements have been during the school year, and also a skills test to see expertise in carrying out practicums. This research aims to see the relationship between anxiety levels and learning outcomes in skills competency tests. The skills competency test is carried out by inviting industry parties to help carry out the assessment. The sample used at Al Islam Productive Vocational School was 20 students, a cross sectional approach was used using total sampling and the Pearson test to determine whether there was a relationship between the two variabels. The instruments used were the HARS anxiety scale and skills competency test scores. The research was carried out over a period of approximately 2 weeks. Using the level of anxiety and the value of learning outcomes in the skills competency test are the data used for research. The results of the normality test show a value of more than 0.005, namely that the data is normally distributed. The Pearson test has a value of -0.800. The analysis shows that there is a significant negative relationship between anxiety levels and learning outcomes in skills competency test scores. The higher the level of anxiety, the lower the student learning outcomes.